PERKAWINAN KATOLIK DAN TRADISI RAMPANAN KAPA’ DI TORAJA DALAM ANALISIS KOMPARATIF - Michael Reskiantio Pabubung (Jurnal Euntes, 2022)
ABSTRACT Marriage is an important encounter in one’s life. In various cultures, marriage contains many signs and symbols that express the appreciation of marital life. Both signs and symbols, as well as marital values, are very interesting “locus theologicus” to study, likewise with Toraja culture. There is a concept of marriage in Toraja culture known as “rampanan kapa’”. In “rampanan kapa’” there is an interesting Toraja marriage value, namely “basse situka’”. “Basse” means pledge, and “situka’” means exchanging. “Basse situka’” is an exchange of pledges. The exchange of the parents of the bride and groom symbolizes the exchange of pledges. The contents of the pledge in basse situka’ are lifelong fidelity and not open to divorce. Based on the theological findings from this local culture through qualitative research using literature review techniques, the author has found a connection between the “basse situka’” concept of marriage in the Toraja tradition and the concept of the sacramentality of marriage in the Catholic Church. Even so, there is still a significant difference, especially regarding the tendency of non-monogamous “rampanan kapa’". In the Catholic understanding of marriage, the Church firmly says that the essential nature of marriage is monogamous and indissolubility.